2017
DOI: 10.1016/j.athoracsur.2017.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multidisciplinary Program to Expedite Care of Esophageal Emergencies

Abstract: Development of an esophageal emergency referral program has facilitated multidisciplinary care at a high-volume institution, and early outcomes appear favorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Our recommendation for obtaining an esophagram prior to transfer when able is supported by previous studies. Ceppa et al ( 10 ) reviewed patients transferred to their institution with suspected esophageal perforation. The authors found that a proportion (46%, n=33/71) of patients transferred due to pneumomediastinum were subsequently found to have no esophageal perforation on esophagram.…”
Section: Discussionmentioning
confidence: 99%
“…Our recommendation for obtaining an esophagram prior to transfer when able is supported by previous studies. Ceppa et al ( 10 ) reviewed patients transferred to their institution with suspected esophageal perforation. The authors found that a proportion (46%, n=33/71) of patients transferred due to pneumomediastinum were subsequently found to have no esophageal perforation on esophagram.…”
Section: Discussionmentioning
confidence: 99%